World Haptics 2009 - Third Joint EuroHaptics Conference and Symposium on Haptic Interfaces for Virtual Environment and Teleoper 2009
DOI: 10.1109/whc.2009.4810862
|View full text |Cite
|
Sign up to set email alerts
|

A 2D haptic glyph method for tactile arrays : Design and evaluation

Abstract: We present a new framework for information cue rendering on 2D vibrotactile arrays, and we describe an experiment that investigated the feasibility of our approach. The methods are broadly applicable, but our work is motivated by the potential for a tactile array to provide an additional useful channel for information such as location cues related to dataset features or remote user behaviors in visualization systems. Our experiment measured the accuracy with which three basic haptic glyph parameters (position,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…Borst and Asutay [2005] constructed a low-resolution vibrotactile array with a vibration motor [Vibration Motor 2012] as a means to communicate a sense of touch. They constructed a thirty-element vibrotactile array as a means to communicate sketches [Lipari and Borst 2010; Borst and Baiyya 2009]. We have used a vibration motor and a methodology similar to Borst and Asutay [2005] to construct our tactile display.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Borst and Asutay [2005] constructed a low-resolution vibrotactile array with a vibration motor [Vibration Motor 2012] as a means to communicate a sense of touch. They constructed a thirty-element vibrotactile array as a means to communicate sketches [Lipari and Borst 2010; Borst and Baiyya 2009]. We have used a vibration motor and a methodology similar to Borst and Asutay [2005] to construct our tactile display.…”
Section: Related Workmentioning
confidence: 99%
“…The first method is to use one tactile actuator with temporal-order encoding or different waveforms to represent information [Maclean and Enriquez 2003]. The second method is to increase the number of tactile actuators and use different patterns (shapes) to represent information [Borst and Baiyya 2009]. Usability of the tactile medium depends on the ability of users to distinguish the tactile codes represented by waveforms/shapes [MacLean 2008].…”
Section: Introductionmentioning
confidence: 99%
“…Borst et al [3] constructed a low resolution vibrotactile array with vibration motor [1] as a means to communicate a sense of touch. They constructed a 30 element vibrotactile array as a means to communicate sketches which act like touch [12,4]. We have used vibration motor and a methodology similar to Borst et al [3] to construct our tactile display.…”
Section: Related Workmentioning
confidence: 99%
“…The first method is to use one tactile actuator and temporal order encoding or different waveforms to represent information [13]. The second method is to increase the number of tactile actuators and use different patterns (shapes) to represent information [4]. Usability of a tactile interface depends on the ability of users to distinguish the tactile codes represented by waveforms/shapes [14].…”
Section: Introductionmentioning
confidence: 99%
“…Sensory saltation is affected by several factors such as the two-point discrimination threshold in the distance between actuators(TPDT), inter stimuli interval (ISI), saltatory area, and repetition [11]. Borst and Baiyya [3] investigated the recognition accuracy of three parameters (position, direction, and intensity) in a two-dimensional tactile display and revealed that people can interpret multiple parameters in combination.…”
Section: Tactile Perception and Tactile Uismentioning
confidence: 99%